2016
DOI: 10.1007/s12649-016-9667-1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Anaerobic Digestion Effluents (ADEs) Used as the Nutrient Sources for Chlorella sp. Cultivation on Fermentative Biogas Production

Abstract: Purpose This study investigated the chemical characteristics and anaerobic digestion of Chlorella sp. microalgae cultivated on various anaerobic digestion effluents (ADEs) as a nutrient medium. Chlorella sp. was grown in anaerobically digested effluent of dairy wastewater (DW), municipal wastewater sludge (WS), maize silage and swine slurry, and cattle manure (CM). Methods To evaluate the anaerobic biodegradability of harvested biomass, 20-days batch anaerobic digestion experiments were used. Results It was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…It has also been found that biomass can even grow better, and the culture is more homogeneous because other algae species do not tolerate leachate as well [61][62][63].…”
Section: Methodsmentioning
confidence: 99%
“…It has also been found that biomass can even grow better, and the culture is more homogeneous because other algae species do not tolerate leachate as well [61][62][63].…”
Section: Methodsmentioning
confidence: 99%
“…Digested sludge is then centrifuged to separate the solids and liquid fraction otherwise called reject water. Reject water can contain a COD concentration ranging from 1000 to 8000 mg/L [31] depending on the type of feed and efficiency of biogas tank.…”
Section: Proposed Ad-mes Integrated Systemmentioning
confidence: 99%
“…Currently, the use of liquid digestate as a substrate for microalgae growth medium has attracted much attention as a wastewater treatment technology with the simultaneous sustainable microalgae biomass feedstock production [10][11][12][13]. Microalgae have the ability to efficiently utilize nutrients from liquid fraction of digestate, and mixotrophic cultivation may enhance inorganic and organic carbon removal, while providing biomass for bioenergy applications [8].…”
Section: Introductionmentioning
confidence: 99%